Struktur, Fungsi dan Makna Mantra Pengobatan di Desa Tanjung Kurung Ulu Kecamatan Tanjung Tebat Kabupaten Lahat - Karuniawan, M. Bakti; Missriani, Missriani; Effendi, Darwin (Indonesian Research Journal on Education, 2023)
This study aims to describe the structure, function, and treatment of the meaning of mantras in Tanjung Kurung Ulu Village, Tanjung Tebat District, Lahat Regency. The research method uses a qualitative descriptive method. Collecting data using observation, interviews, and recordings. The technique of analyzing the data in this research is the systematic editing of data from interviews, field notes, and documentation, by categorizing the data, describing it in search units, selecting important data to make, and drawing conclusions that are easily accessible to oneself and others. Results Based on data analysis conducted on 13 treatment spells, the following results were obtained. In the 13 spells studied there is aspell structure, namely the title, opening, suggestion, and closing elements, with the function of the spell there are 13 spells that function as treatment, healing, and relieving pain experienced by a person. While the meaning of the mantra contained in the 13 spells has a denotative meaning.